Legal regulation of bankruptcy court proceedings and order of their application. - Заболотній, Сергій Володимирович (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2010)
In this article an author pays regard to legal relationships in the sphere of insolvency. In obedience to a current legislation in detail analyses judicial procedures which can be used to the debtor in realization of businesses about bankruptcy, and also determines the ways of their application and improvement.